2014
DOI: 10.29252/ijn.27.90.91.83
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Student Nurses’ Experiences in Clinical Environment: Vertical Violence

Abstract: Background & Aim: Clinical practice is an important part of the educational curriculum of nursing students. Effective and dynamic interactions among the students, health care providers, instructors, and the clinical environment and its elements affect their professional development. The aim of this report as a part of a more extensive research is describing the negative experiences of nursing students in the clinical environment. Material & Methods: It was a qualitative study. Data was collected by purposeful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These findings were lower than the NESS mean scores obtained from the other studies conducted in Turkey (Bahadır -Yılmaz, 2016;Karabulutlu et al, 2019;Küçükakça et al, 2017;Ozsaban et al, 2019;Tarsuslu et al, 2020;Yıldırım et al, 2016). In accordance with the findings of these studies, students reported that they were not supported in clinical settings (Dinmohammadi et al, 2014). Nursing students were vulnerable in the clinical setting in terms of vertical violence from nurses.…”
Section: Discussionsupporting
confidence: 81%
“…These findings were lower than the NESS mean scores obtained from the other studies conducted in Turkey (Bahadır -Yılmaz, 2016;Karabulutlu et al, 2019;Küçükakça et al, 2017;Ozsaban et al, 2019;Tarsuslu et al, 2020;Yıldırım et al, 2016). In accordance with the findings of these studies, students reported that they were not supported in clinical settings (Dinmohammadi et al, 2014). Nursing students were vulnerable in the clinical setting in terms of vertical violence from nurses.…”
Section: Discussionsupporting
confidence: 81%
“…In a qualitative study, nursing students' experiences regarding vertical violence in clinical settings showed that as one of the major challenges of student support, this kind of violence has numerous and varied evidences including humiliating and blaming students, rejection, exploitation, discrimination, bullying, and poverty of student supporting. [ 16 ] Furthermore, a review introduced the following factors as the challenges of clinical education: lack of access to educators, inappropriate behavior of ward staff, lack of student and educator support, and student bewilderment in the absence of educator. [ 17 ] Nursing students' experiences of emotional challenges during clinical education in Malawi (East Africa) showed that due to the insufficiency in nursing staff, students are often left alone at the bedside, not receiving support from nurses and/or educators.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, exploitation, discrimination, and bullying by educators and treatment staff were cited as challenges, which need support. [ 16 ] Regarding identity problems of nursing profession, a study in South Africa indicated that male students confront with more challenges at the bedside, simply because nursing is a female-dominated profession, and there are few male nurses. [ 31 ] Concerning culture, patients' lack of cooperation and trust in students, even in teaching hospitals, is another problem of clinical education which requires support from the system and educators.…”
Section: Resultsmentioning
confidence: 99%
“…Humiliating experiences were another concept identified in this study, as the majority of the participants reported the unfriendly behaviors of the physicians and staff and sometimes of the instructors towards the midwifery students. Unfriendly behaviors included a wide range of verbal abuse, bullying and disrespect, and threatened the students' health in clinical training settings (17). The clinical setting did not support the students, and was referred to as the phenomenon of "vertical violence against students" (18).…”
Section: Discussionmentioning
confidence: 99%